Ultimate study guide : foundations - Microsoft project 2013 - Howard, Dale A. (Chefetz LLC dba MSProjectExperts New YorkUS, 2013)
Presents a reference manual for the Microsoft Project 2013 desktop application. Teaches how to define a new project, plan a project with tasks, resources and assignments, analyse the Critical Path, baseline a project, report on the project and then close the project. Includes information notes, warnings and best practices.